2012
DOI: 10.1055/s-0032-1314976
|View full text |Cite
|
Sign up to set email alerts
|

Cassane-type Diterpenes from the Seeds of Caesalpinia minax with Their Antineoplastic Activity

Abstract: Five new cassane-type diterpenes, neocaesalpin AA (1), neocaesalpin AB (2), neocaesalpin AC (3), neocaesalpin AD (4) and neocaesalpin AE (5), were isolated from Caesalpinia minax together with three known compounds, 12α-methoxyl,5α,14β-dihydroxy-1α,6α,7β-triacetoxycass-13(15)-en-16,12-olide (6), spirocaesalmin (7) and magnicaesalpin (8). Their structures were elucidated based on 1D and 2D NMR, MS and CD analyses. Compounds 1-6 were tested against Hela, HCT-8, HepG-2, MCF-7 and A549 cancer cells and showed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Only several cassane‐type diterpenoids were reported with cytotoxic activity ( Supporting Information , Figure S99 ), including caesalpinolides A and B, [31] caesalpins A−D, [21] neocaesalpins S−V, [32] phanginin R, [16] neocaesalpins AA−AC [33] and 12 α ‐methoxy‐5 α ,14 β ‐dihydroxy‐1 α ,6 α ,7 β ‐triacetoxycass‐13(15)‐en‐16,12‐olide [33] . Taken together, the preliminary structure‐activity relationship could be summarized as following: the presence of an acetoxy group at C‐7 or a hydroxy group at C‐6 could decrease the cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Only several cassane‐type diterpenoids were reported with cytotoxic activity ( Supporting Information , Figure S99 ), including caesalpinolides A and B, [31] caesalpins A−D, [21] neocaesalpins S−V, [32] phanginin R, [16] neocaesalpins AA−AC [33] and 12 α ‐methoxy‐5 α ,14 β ‐dihydroxy‐1 α ,6 α ,7 β ‐triacetoxycass‐13(15)‐en‐16,12‐olide [33] . Taken together, the preliminary structure‐activity relationship could be summarized as following: the presence of an acetoxy group at C‐7 or a hydroxy group at C‐6 could decrease the cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The HRESIMS of 2 indicated the molecular formula as C 22 Tables 1 and 2, also see Supplementary Materials) were very similar to those of caesaljapin methyl ester [20]. In the HMBC spectrum, the correlations from the singlet methyl group (δ H 0.74, s) to C-1 (δ C 39.1), C-5 (δ C 50.5), C-9 (δ C 45.2) and C-10 (δ C 37.0) assigned it as Me-20.…”
Section: Identification Of New Compoundsmentioning
confidence: 99%
“…The HRESIMS of 4, exhibiting the ion peak at m/z 399.1787 [M + Na] + , established the molecular formula as C 21 H 28 O 6 . The UV and IR spectra showed absorptions for a hydroxy group (3436 cm´1) and an α,β-unsaturated butenolide moiety (210 nm; 1729 cm´1) [16,22]. The olefinic proton signal at δ H 5.67 (s, H-15) and downfield carbon signals at δc 79.6 (C-12), 175.5 (C-13), 110.9 (C-15) and 174.0 (C-16) in the NMR spectra further supported the presence of the α,β-unsaturated butenolide moiety (Tables 1 and 2 (Table 1).…”
Section: Identification Of New Compoundsmentioning
confidence: 99%
“…Previous studies have shown that this plant contains several classes of compounds, such as diterpenes, triterpenoids, flavonoids, steroids, and phenolic compounds . Among the isolated structures, diterpenes are a group of highly structurally diverse compounds and show significant biological activities, such as antimalarial, antiproliferative, antihelmintic, antibacterial, and antineoplastic effects . Because of these extensive activities, we carried out studies of the cassane diterpenes of the seeds of C. decapetala .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Among the isolated structures, diterpenes are a group of highly structurally diverse compounds and show significant biological activities, such as antimalarial, antiproliferative, antihelmintic, antibacterial, and antineoplastic effects. [5][6][7] Because of these extensive activities, we carried out studies of the cassane diterpenes of the seeds of C. decapetala. During the course of this work, five cassane-type diterpenes were isolated from the CHCl 3 extract of C. decapetala, among which caesaldecapes C and D (1-2) were identified as new compounds.…”
Section: Introductionmentioning
confidence: 99%